The Stock Market Reactions to DomesticJoint Venture Announcements:The Malaysian Experience - Abdul Aziz, Azah Najwa (2005)
This study examines the stock market’s reactions to domestic joint venture announcements. It focuses on the Malaysian market and economy, and how corporate members, i.e. firm managers and investors perceive the announcements of joint venture formations. 75 Malaysian public listed companies that involved in 35 joint ventures are selected and examined. A few alternative hypotheses concerning the stock market’s reactions to domestic joint venture announcements are tested. The Wealth Effect Hypothesis shows that the announcements bring no significant impact on the stock market. However, by standardising the data, the stock market’s reactions to the announcements are significantly negative. The Relative Firm Size Hypothesis supports previous studies by showing that small and big firms’ returns are significantly different, and relatively smaller firms incur larger magnitude, and negative stock market reaction. The findings of the above two cases also support the Rational Expectations and Institutional Investors hypotheses respectively. These hypotheses signal the perception of investors in firms’ strategic investment decisions. The rest of the alternative hypotheses test the relationship between the stock market’s returns with three other variables that include Tobin’s q-ratio that measure investment opportunities, absolute firm size, and level of free cash flows. Observation depicts significant inverse relationships between Tobin’s q and absolute firm size level with the stock market reactions, while level of free cash flow has no significant power in explaining the variability of market returns. On the other hand, the results also show signs of market inefficiencies and immaturities. The insignificance and inconsistencies of these findings to the predicted hypotheses may be explained by the characteristics of the Malaysian economy.